Female athletes and eating disorders - Soubliere, D.; Gitimu, P. N. (The Sport Journal, 2012)
Sports should prevent athletes from having eating disorders not develop eating disorders. There is evidence that female athletes are at a risk of developing disordered eating. The purpose of this study was to find how prevalent eating disorders are in female athletes and examine factors that may have a relationship with eating disorders.